2022
DOI: 10.1029/2021jd035579
|View full text |Cite
|
Sign up to set email alerts
|

The Illumination of Thunderclouds by Lightning: 1. The Extent and Altitude of Optical Lightning Sources

Abstract: Lightning flashes are comprised of vast networks of hot ionized plasma channels (da Silva et al., 2019) that extend over tens or even hundreds of kilometers (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 57 publications
5
19
0
Order By: Relevance
“…We propose that altitude information can be extracted from GLM measurements of how the surrounding thunderclouds are illuminated by lightning. Our previous modeling work (Peterson, 2020a ) demonstrated that low‐altitude sources result in different spatial radiance patterns than high‐altitude sources regardless of cloud geometry, and this was confirmed with GLM observations in and Part 1 of this series (Peterson et al., 2021a ). Our discussion of “optical repeater” flashes in Peterson et al.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…We propose that altitude information can be extracted from GLM measurements of how the surrounding thunderclouds are illuminated by lightning. Our previous modeling work (Peterson, 2020a ) demonstrated that low‐altitude sources result in different spatial radiance patterns than high‐altitude sources regardless of cloud geometry, and this was confirmed with GLM observations in and Part 1 of this series (Peterson et al., 2021a ). Our discussion of “optical repeater” flashes in Peterson et al.…”
Section: Introductionsupporting
confidence: 79%
“…Our discussion of “optical repeater” flashes in Peterson et al. ( 2021a ) and previous analyses of groups with complex spatial radiance distributions (Peterson, 2020b ) further showed that radiance patterns were consistent between subsequent illuminations of the same cloud layer. However, these pictures of cloud illumination would change if the flash moved into a different layer, for example, during cases in Peterson et al.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…As the optical emissions from these sources become spread over a larger number of pixels, a smaller fraction of the total pulse signal is used for detection. Since most optical sources are small (Peterson et al, 2022a), the impact on instrument performance is anticipated to depend on the amount of spatial broadening in the signals from scattering in the clouds, further amplifying the existing detection advantage for high-altitude sources (that are less modified by scattering in the cloud medium) over low-altitude sources (that are severely broadened). However, if the low-altitude pulses could still be detected with a finer-resolution instrument, the greater detail in the measured spatial energy distributions would be beneficial for applications that use this product (Peterson, 2019(Peterson, , 2021aPeterson et al, 2022bPeterson et al, , 2022cPeterson & Mach, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is the second part of our thundercloud illumination study. In Part 1 (Peterson et al., 2021a ), we examined how the positions and geometries of optical sources affected GLM measurements of cloud illumination. In Part 2, we shift our focus from the emitter to the GLM instrument and quantify the effects of the GLM threshold on event/group/flash detection, flash clustering, and gridded product generation.…”
Section: Introductionmentioning
confidence: 99%